Analysis of the Effectiveness of Using the ASABRI Mobile Application in Pension Fund Participation and Claims - Nasution, Silpiah Jahra; Nasution, Annio Indah Lestari; Syarvina, Wahyu (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the effectiveness of the ASABRI Mobile application in pension participation and information services. This study uses a qualitative method with a descriptive approach. Informants were determined purposively, consisting of active ASABRI participants, retirees, and heirs. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. Data validity used triangulation techniques. The results show that the ASABRI Mobile application is effective in facilitating participants' access to information and accelerating the process of pension participation and claim services. Obstacles found include low digital literacy among elderly participants and technical problems in using the application.